Study of the loading capacity of main tourist environments of the city of Pedra Bela – SP (Research, Society and Development, 2020)
The growing search for recreational activities in natural environments has led to the need for tourism planning and management, in order to propose an orderly tourism, where damage and impacts caused to visitation sites are minimal, making tourism sustainable. An important tool for tourism planning is the calculation of Tourist Load Capacity, which enables the manager to define indicators and manage the areas where there will be visitation. The area of study of this research is the complex of the Sanctuary of Nossa Senhora Aparecida, located in the municipality of Pedra Bela, São Paulo. The objective of this research was to calculate the tourist load capacity index of the attractions that are part of this Sanctuary, in order to verify if the activities developed in these areas exceed this index or not. The methodology was composed by the application of the Cifuentes method in the Sanctuary area and field work campaigns. The Cifuentes method establishes the best methodology for the areas in question, as it allows the integration of physical, biotic and management factors through the calculations of actual and effective physical carrying capacity. It was concluded that the studied areas do not exceed their Tourist Cargo Capacity and that there is a concern about the environmental impacts by public managers, when in events that may get a possible overload of visitors.